Digital Ethics Among Vocational High School Students: A Systematic Literature Review Of Emerging Issues And Educational Practices - Sitti Hardiyanti Arhas (Asha Publishing, 2026)
This study aimed to analyze the development of research on digital ethics among vocational high school students through a Systematic Literature Review (SLR) based on bibliometric analysis. The study focused on identifying publication trends and bibliometric characteristics, examining major contributors and geographical distributions, and exploring the main themes, emerging issues, and educational practices within the field. Data were collected from the Scopus database using predefined keywords related to digital ethics, digital citizenship, digital literacy, and vocational education, resulting in 37 articles published between 2019 and 2025. Data analysis employed the Analyze Search Results feature in Scopus and VOSviewer software through co-occurrence, overlay, and density visualizations. The findings revealed a growing trend in publications, with Indonesia emerging as the most productive contributor. Furthermore, the intellectual structure of the field has evolved from traditional themes centered on digital literacy and vocational education toward broader issues involving digital citizenship, digital transformation, responsible technology use, and emerging educational practices. These findings indicate that digital ethics has become an essential component of twenty-first-century competencies and technology-supported learning environments in vocational education.